Language variables in administrative health data hosted at ICES - Batista, Ricardo; Prud'homme, Denis; Tanuseputro, Peter; Manuel, Doug (L'institut du Savoir Monfort and ICES Ottawa, 2019)
Research on linguistic minorities have revealed important disparities in Canada. Numerous analyses have identified the need for further studies looking at health status, healthcare utilization access barriers and quality of care affecting francophone living in a minority contexts (FLMCs) in Canada.1 The value and need to improve access and use of valid health information to support the planification of health and social services is well documented; however, important gaps and challenges have been recognized, which limit further progress in understanding the disparities in health and health care for some subpopulations. 2

Sources de données de Statistique Canada sur les minorités de langue officielle (n°91-549 -X) - Lafrenière, Sylvie (Statistique Canada, 2013)

Statistics Canada data sources on official-language minorities (n°91-549-X-n°2) - Lafrenière, Sylvie (Statistics Canada, 2013)

À l’intersection des définitions de langues : portrait des communautés linguistiques au Québec et dans les réseaux territoriaux de services en 2016. La langue, déterminant de l'état de santé et de la qualité des services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

At the intersection of language definitions: A portrait of linguistic communities in Québec and its territorial service networks in 2016. Language as determinant of health and quality of services - Lussier, Marie-Hélène; Tu, Mai Thanh; Blaser, Christine (Institut national de santé publique du Québec, 2019)

Assessment of validity for the “language spoken at home” variable in Québec death records: Summary. Language, determinant of health status and of services' quality - Trempe, Normand; Boivin, Marie-Claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)

La validité de la variable « Langue d’usage à la maison » du Fichier des décès du Québec : synthèse. La langue, déterminant de l'état de santé et de la qualité des services - Trempe, Normand; Boivin, marie-claude; Lo, Ernest; Diogo Barry, Amado (Institut national de santé publique du Québec, 2012)